(untitled) (The Research of Medical Science Review, 2025)
Background: In December 2019, Wuhan, Hubei Province, China, reported an unexplained pneumonia epidemic. The pandemic outbreak caused serious mental health stress for the global population. One of the most important cures of COVID, isolation, posed serious issues to the psychological conditions of population. It not only affected the human psychological conditions; it also posed greater stress to the global health system. It undermined the overall health system globally and caused serious problem for healthcare officials and other personals (Galanopoulos, Gkeros et al. 2020). Material and methods: The sample will be collected by questionnaire. The study will be a retrospective cohort study. The research will be conducted over 6 months after the synopsis is approved. Here is the list of complete materials included to complete the study. Result: Seropositivity of ELISA across studies: 85%-95%.Rate of positivity of PCR in covid-19 patients: 70% initially while increased to 99% afterwards.Rates of ICT in covid-19 patients: Rapid antigen test: 72% in symptomatic patients while 58% in asymptomatic patients.Rapid antibody tests: 75%-85% positivity rate. Conclusion: According to research, ELISA has an 85–95% sensitivity for detecting IgG throughout this time, which makes it a very useful tool for seroprevalence studies and immune response evaluation. PCR exhibits remarkable performance characteristics with sensitivity rates of 95–98% and specificity surpassing 99%, making it the most sensitive molecular detection technique now in use. (Wang, Xu et al. 2020). Antigen-detecting ICTs (RATs) is directly related to viral load, with optimal sensitivity (70-90%) occurring during the peak infectious period which is usually days 1–7 after the onset of symptoms. Since this window corresponds with the highest risk of transmission RATs are very helpful in locating contagious people in public places. The performance profile of antibody-detecting ICT formats varies; IgM tests show a positive result 7–14 days after infection (60–80% sensitivity) while IgG tests only exhibit reliability (>85%) after 14 days.